2012
DOI: 10.1177/1040638712466395
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of fecal DNA extraction kits for the detection of Mycobacterium avium subsp. paratuberculosis by polymerase chain reaction

Abstract: Abstract. Culture of Mycobacterium avium subsp. paratuberculosis (MAP) from feces has been considered the gold standard for the diagnosis of paratuberculosis for many years. However, direct fecal polymerase chain reaction (PCR) is becoming more widely used, demonstrating similar sensitivity and specificity to culture. To ensure efficient and reproducible PCR results from a difficult sample matrix such as feces, there are many obstacles that a DNA extraction method must overcome, including the presence of inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 21 publications
2
59
2
Order By: Relevance
“…The para-JEM medium (Thermo Fisher Scientific [TREK Diagnostic Systems, Inc.], Cleveland, OH) was supplemented according to the manufacturer's instructions, inoculated with 500 l of decontaminated milk sample, and placed into the ESP Culture System II machine for up to 65 days. All bottles were subjected to MAP growth confirmation procedures of Ziehl-Neelsen acid fast stain for MAP colonies and PCR of the IS900 gene target as previously described (17). HEY medium (BD) was inoculated with 100 l of decontaminated milk sample and incubated at 39°C for 12 weeks, and colonies were counted.…”
mentioning
confidence: 99%
“…The para-JEM medium (Thermo Fisher Scientific [TREK Diagnostic Systems, Inc.], Cleveland, OH) was supplemented according to the manufacturer's instructions, inoculated with 500 l of decontaminated milk sample, and placed into the ESP Culture System II machine for up to 65 days. All bottles were subjected to MAP growth confirmation procedures of Ziehl-Neelsen acid fast stain for MAP colonies and PCR of the IS900 gene target as previously described (17). HEY medium (BD) was inoculated with 100 l of decontaminated milk sample and incubated at 39°C for 12 weeks, and colonies were counted.…”
mentioning
confidence: 99%
“…In addition, the procedure for the extraction of fecal DNA in preparation for PCR has become easier and less expensive in the recent years (Stabel et al, 2004). Considering an effective method to ensure a complete-DNA extraction, a mechanical disruption step (bead-beating) was included -which breaks up bacterial cell wall mechanically by vibrating bacteria at high speed, in addition to the commercial kit protocol (Odumero et al, 2002;Zecconi et al, 2002;Herthnek, 2009) improving the sensitivity of the protocol applied, also reported by Leite et al (2013) with the comparable performance results.…”
Section: Discussionmentioning
confidence: 99%
“…DNA from individual fecal samples was extracted according to the following procedure reported previously by Leite et al (2013) using a commercial DNA preparation kit (ZR Fecal DNA Kit™, Zymo Research, Irvine, CA, USA). Processing was done according to kit´s protocol for isolation of nucleic acids from bacteria and yeast.…”
Section: Dna Isolation From Individual Fecal Samplesmentioning
confidence: 99%
“…Thus, commercial kits for DNA extraction would detect MAP from feces with high sensitivity without cultivating bacteria [37] . Bead beating in a lysis solution for cell distruption as well as use of spin column technology can perform more effective DNA extraction especially from fecal samples [38] . In this study, DNA extraction was also conducted by commercial kit supported with lysis solution and spin column technology for the most accurate diagnosis of MAP.…”
Section: Discussionmentioning
confidence: 99%